Trunk flexion to extension strength ratio of 11- to 18- year old youth ski racers: Data from 15 years of talent development in Austria - Steidl-Müller, L.; Patterson, C.; Luchner, R.; Ebenbichler, C.; Hildebrandt, C.; Raschner, C. (Journal of Science in Sport and Exercise, 2021)
Purpose: The aim of the present study was to evaluate the trunk strength capacity of alpine ski racers aged 10-18 years, who were tested during the last 15 years, to identify reference values for trunk flexor to extensor strength ratios according to age and sex. Methods: In total, 2841 participants (1605 males, 1236 females; 10-18 years) were included, who were pupils of a famous skiing-specific secondary modern school or members of the provincial ski team between 2006 and 2020. The maximum isometric trunk flexion and extension strength was measured using the slightly modified Back Check. Sex-specific differences were assessed with Student`s t test or Mann-Whitney-U test. Univariate analyses of variance or Kruskal-Wallis-H tests were used to assess differences between age groups. Descriptive sex- and age-specific reference values were calculated (norm area: mean ± ½ standard deviation). Results: Sex-specific differences were found for both flexion (starting at 11 years) and extension strength (starting at 12 years) (P < 0.001). Lower flexion to extension strength ratios were identified for males (0.89 ± 0.18) compared with females (0.82 ± 0.15), but the ratios remained constant across age groups for both sexes. Conclusion: The present study provides age- and sex-specific reference values for trunk flexion to extension strength ratios for 10- to 18-year old youth and adolescent ski racers. The data of the present study represent a large data pool of youth ski racers at a high-performance level; thus, coaches can use the reference values for comparing the ratios of their athletes.